Positive electrode slurry and preparation method thereof, and lithium battery positive plate prepared from positive electrode slurry
The positive electrode slurry is prepared by two steps of dry mixing and wet mixing, which solves the problem of uneven dispersion of conductive agents, forms a stable three-dimensional conductive network, and realizes the "double-high" characteristics of high energy density and high power density of lithium batteries. .
Patent Information
- Application Number
- CN202411682292.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-21
AI Technical Summary
The positive electrode slurry of existing lithium batteries is prone to settle during the stirring process, resulting in uneven dispersion of conductive agent materials, affecting the rapid propagation of ions and electrons, and limiting the electrical performance of the battery's rapid charging and discharging under large currents.
The positive electrode slurry is prepared by two steps of dry mixing and wet mixing. First, the positive electrode active material, conductive agent and adhesive are stirred and mixed through the dry mixing step to form a powder ball, and then a dispersant and solvent are added to the wet mixing step to form a stable three-dimensional conductive network through stirring.
The stability and uniformity of the positive electrode slurry are achieved, the uniform dispersion of conductive agents is promoted, and an efficient three-dimensional conductive network is formed, which improves the "double-high" characteristics of high energy density and high power density of lithium batteries.
Smart Images

Figure CN119495715A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a positive electrode slurry and a preparation method thereof, and a positive electrode sheet of a lithium battery prepared using the positive electrode slurry. Background Art
[0002] In order to meet the growing demand for high-energy, high-power density electrified equipment and vehicles, high-quality load electrodes with high area capacity and low resistivity have attracted the attention of researchers. However, when meeting the "double high" requirements of the battery, the thinner electrode sheet has a large resistivity, which limits the battery's electrical performance of rapid charging and discharging under large currents and cannot achieve high-power performance. This is mainly because the positive electrode slurry is prone to sedimentation during stirring, resulting in uneven dispersion, so that the conductive agent materials such as carbon black and carbon nanotubes in the slurry cannot form a uniform 3D cross-linked network between the active materials, affecting the rapid propagation of ions and electrons.
[0003] Patent CN110797536 A discloses a positive electrode slurry for lithium-ion batteries, a preparation method thereof, and a lithium-ion battery, wherein the electrical performance of lithium-ion batteries is improved by changing the order of adding different substances in the positive electrode slurry, adjusting the stirring time, stirring speed, and proportion of ingredients, and using a dispersant to process and modify the positive electrode slurry, wherein the composite conductive agent forms a conductive network. However, the introduction of a large amount of composite conductive agent will reduce the mass proportion of the positive electrode active material, which is not conducive to the preparation of low-bending and high-surface-area mass-loaded electrodes.
[0004] Patent CN115692606A discloses a polymer-modified positive electrode sheet and its preparation method, and a lithium battery, wherein a cross-linked phosphonate polymer forms a 3D cross-linked network on the surface of the positive electrode sheet and / or in the gaps between the positive electrode active materials, thereby improving the electrochemical performance and safety of the lithium battery. However, no solvent is added during the preparation of the positive electrode sheet, which is not suitable for wet sheeting, is prone to agglomeration, and cannot ensure uniform dispersion of the conductive agent. Summary of the invention
[0005] The present invention aims to provide a method for preparing positive electrode slurry to achieve stability and uniformity of the slurry, which can be used to prepare soft-pack batteries that can meet high energy density while also having high power density, thereby achieving the "double high characteristics" of the battery.
[0006] A method for preparing a positive electrode slurry in this scheme includes the following steps:
[0007] S1, dry mixing: adding the positive electrode active material, the conductive agent and the binder, stirring and mixing to obtain a powder, and then adding N-methyl-2-pyrrolidone to knead to obtain a dough;
[0008] S2. Wet mixing: Add a dispersant and N-methyl-2-pyrrolidone to the powder mass obtained in S1 and stir to obtain a positive electrode slurry.
[0009] Furthermore, the mass ratio of the positive electrode active material, the conductive agent and the binder is 88-98:1-6:1-6;
[0010] The positive electrode active material is selected from one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and nickel cobalt lithium manganese oxide;
[0011] The conductive agent is selected from one or more mixtures of carbon nanotube powder, carbon nanotube dispersion, conductive carbon black, conductive graphite, acetylene black, and graphene;
[0012] The adhesive is polyvinylidene fluoride.
[0013] Furthermore, the amount of N-methyl-2-pyrrolidone added in S1 is 75% of the amount of the powder.
[0014] Furthermore, the dispersant in S2 is a polyolefin diluted with N-methyl-2-pyrrolidone, and the volume ratio of polyolefin to N-methyl-2-pyrrolidone is 1:500-2000.
[0015] Furthermore, the final liquid-to-solid ratio in S2 is 45%, and the stirring speed during the addition is 70 rpm for rotation and 3000 rpm for revolution, and the time is 3 hours.
[0016] Furthermore, the viscosity of the positive electrode slurry in S2 is 5000-8000 mPa.s.
[0017] Furthermore, the positive electrode active material, conductive agent and binder in S1 are added to the mixer twice for mixing, with an interval of 30 minutes. The stirring speed during the addition is 30 rpm and 500 rpm. After all the powders are added to the mixer, dry mix them at a speed of 30 rpm and 4000 rpm for 60 minutes; the stirring speed during kneading is 70 rpm and 3000 rpm, and the stirring is carried out for 4 hours.
[0018] On the one hand, the present invention also provides a positive electrode slurry prepared by the above method.
[0019] On the other hand, the present invention also provides a lithium battery positive electrode sheet, which is obtained by passing the positive electrode slurry obtained by the above method through a 200-mesh sieve, placing it on a coating machine to coat the aluminum foil current collector on both sides, passing through three temperature zones and then drying, wherein the temperatures in the three temperature zones are 85°C, 90°C, and 80°C, respectively; the drying temperature is 140°C, and the time is 48 hours.
[0020] The beneficial effects of the present invention include:
[0021] 1. Dry mixing, kneading and stirring solve the problem of easy agglomeration of high specific surface area and polycrystalline positive electrode active materials during slurry preparation through the interaction between particles; wet mixing and stirring controls the liquid-to-solid ratio, viscosity and other parameters of the slurry by adding N-methyl-2-pyrrolidone (NMP) to achieve the stability and uniformity of the final slurry.
[0022] 2. During the wet mixing process, the added dispersant polyolefin helps to evenly disperse the conductive agent and build a unique three-dimensional conductive network, which not only reduces the path length of Li+ or electron transmission during the charging and discharging process, allowing ions / electrons to propagate quickly and reduce polarization, but also increases ion diffusion and conductivity.
[0023] 3. The prepared soft-pack battery has both high energy density and high power density, achieving the "double high" characteristics of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The following are scanning electron microscope images of the positive electrode sheets obtained in Examples 2, 4 and 6 of the present invention.
[0025] Figure 2 The discharge curves of soft-pack batteries prepared from the positive electrode sheets obtained in Examples 2, 4 and 6 of the present invention and the positive electrode sheets obtained in the comparative example at 1C.
[0026] Figure 3 The positive electrode sheets obtained in Examples 2, 4 and 6 of the present invention and the positive electrode sheets obtained in the comparative example are assembled into 0.5Ah batteries and subjected to pulse discharge curves at a current of 1000C. DETAILED DESCRIPTION
[0027] The following is further described in detail through specific implementation methods:
[0028] Example 1, a method for preparing a positive electrode slurry, the preparation process is as follows:
[0029] S1. Dry mixing: Weigh 2000g LiCoO2 material, 58.7g conductive carbon black, and 50g polyvinylidene fluoride and stir them twice in a planetary mixer pot. Stir at 30rpm and 500rpm for the first time. After 30min, add all the powders and dry mix them at 30rpm and 4000rpm for 60min. After stirring, add 702g NMP (N-methyl-2-pyrrolidone) to the dry mixed powder, stir at 70rpm and 3000rpm for 4h, and knead into a dough.
[0030] S2, wet mixing: add 1582g NMP organic solvent and polypropylene to the kneaded powder mass after the above mixing, wherein the polypropylene is first diluted with NMP, and the polypropylene:NMP=1:2000 is diluted and then added, and the stirring rate during the addition is 70rpm for rotation and 3000rpm for revolution for 3h at high speed. After the end, the final slurry viscosity is 7329mPa.s, that is, the viscosity meets the coating requirements.
[0031] Embodiment 2, a positive electrode sheet of a lithium battery
[0032] Specifically, the slurry obtained in Example 1 was passed through a 200-mesh sieve and then transferred to a coating machine for double-sided coating of the aluminum foil current collector. The coating and drying temperatures (three temperature zones) were: 85°C, 90°C, and 80°C. The current collector was 12-micron aluminum foil. The surface density of the electrode was 1.6 g / m 2 Then the electrode was dried at 140℃ for 48h to finally obtain a high-quality electrode.
[0033] Embodiment 3, a method for preparing a positive electrode slurry, the preparation process is as follows:
[0034] S1. Dry mixing: Weigh 1500g LiCoO2 material, 27.15g conductive carbon black, and 36.7g polyvinylidene fluoride and stir them twice in a planetary mixer pot. Stir at 30rpm and 500rpm for the first time. After 30min, add all the powders and dry mix them at 30rpm and 4000rpm for 60min. After stirring, add 430g NMP and 590g single-walled carbon nanotube dispersion to the dry mixed powder, stir at 70rpm and 3000rpm for 4h, and knead into a dough.
[0035] S2, wet mixing: add 1481g NMP organic solvent and polypropylene to the kneaded powder mass after the above mixing, wherein the polypropylene is first diluted with NMP, and the polypropylene:NMP=1:1000 is diluted and then added, and the stirring rate during the addition is 70rpm for rotation and 3000rpm for revolution for 3h at high speed. After the end, the final slurry viscosity is 6257mPa.s, which meets the coating requirements.
[0036] Example 4, a positive electrode sheet for a lithium battery
[0037] Specifically, the slurry obtained in Example 3 was passed through a 200-mesh sieve and then transferred to a coating machine for double-sided coating of the aluminum foil current collector. The coating and drying temperatures (three temperature zones) were: 85°C, 90°C, and 80°C. The current collector was 12-micron aluminum foil. The surface density of the electrode was 1.6 g / m 2 Then the electrode was dried at 140℃ for 48h to finally obtain a high-quality electrode.
[0038] Example 5, a method for preparing a positive electrode slurry, the preparation process is as follows:
[0039] S1. Dry mixing: Weigh 1000g LiCoO2 material, 13.75g conductive carbon black, 18.45g polyvinylidene fluoride and 15g carbon nanotube powder and stir them twice in a planetary mixer pot. Stir at 30rpm and 500rpm for the first time. After 30min, add all the powders and dry mix them at 30rpm and 4000rpm for 60min. After stirring, add 359g NMP to the dry mixed powder, stir at 70rpm and 3000rpm for 4h, and knead into a dough.
[0040] S2, wet mixing: add 920.9g NMP organic solvent and polypropylene to the kneaded powder mass after the above mixing, wherein the polypropylene is first diluted with NMP, and the polypropylene:NMP=1:500 is diluted and then added, and the stirring rate during the addition is 70rpm for rotation and 3000rpm for revolution for 3h at high speed. After the end, the final slurry viscosity is 7658mPa.s, which meets the coating requirements.
[0041] Embodiment 6, a positive electrode sheet of a lithium battery
[0042] Specifically, the slurry obtained in Example 5 was passed through a 200-mesh sieve and then transferred to a coating machine for double-sided coating of the aluminum foil current collector. The coating and drying temperatures (three temperature zones) were: 85°C, 90°C, and 80°C. The current collector was 12-micron aluminum foil. The surface density of the electrode was 1.6 g / m 2 Then the electrode was dried at 140℃ for 48h to finally obtain a high-quality electrode.
[0043] The difference between the comparative example and Example 2 is that the positive electrode slurry used is not added with a polypropylene dispersant during the preparation process, as follows:
[0044] Weigh 2000gLiCoO2 material, 58.7g conductive carbon black, and 50g polyvinylidene fluoride and stir them in a planetary mixer pot twice. Stir at 30rpm and 500rpm for the first time. After 30min, add all the powders and dry mix them at 30rpm and 4000rpm for 60min. After stirring, add 702gNMP to the dry mixed powder, stir for 4h at 70rpm and 3000rpm, and knead into a dough. Add 1582gNMP organic solvent to the kneaded dough after the above mixing, and the stirring rate during the feeding is 70rpm and 3000rpm. High-speed dispersion for 3h. After the end, the final slurry viscosity is 7329mPa.s, which meets the coating requirements.
[0045] The slurry was sieved through a 200-mesh sieve and then transferred to a coating machine. The coating and drying temperatures (three temperature zones) were: 85°C, 90°C, and 80°C. The current collector was a 12-micron aluminum foil. The surface density of the electrode was 1.6 g / m 2 Then the electrode was dried at 140℃ for 48h to finally obtain a high-quality electrode.
[0046] test:
[0047] 1. Test the resistivity of the positive electrode, as shown in Table 1:
[0048] Table 1 Resistivity of positive electrode sheet
[0049]
[0050] The test results in Table 1 show that the addition of dispersant polypropylene organic solvent can reduce the resistivity of the positive electrode sheet. Compared with the addition of a single type of conductive carbon black, the carbon nanotubes added in Examples 2 and 4 are more conducive to forming a three-dimensional conductive network and reducing the resistivity of the positive electrode sheet.
[0051] 2. Electron microscope scanning of the pole piece
[0052] like Figure 1 As shown, according to Figure 1 It can be seen that the comparative positive electrode sheet shows that the gaps between particles are large and the particles are not compact, which makes the lithium ions and electrons incoherent during the transmission process. In Examples 2, 4, and 6, the gaps between the positive electrode sheet particles are filled with conductive agents, forming point-line-surface contact points between the active materials, connecting into an excellent three-dimensional conductive network.
[0053] 3. Discharge test of soft-pack batteries prepared from the positive electrode sheets obtained in Examples 2, 4 and 6 and the positive electrode sheets obtained in the comparative example at 1C
[0054] The positive electrode sheets prepared in Example 2, Example 4, Example 6 and the comparative example were assembled into soft-pack batteries with high-quality negative electrode sheets and subjected to 1C discharge treatment (voltage range 2.5-4.2V). The discharge curves are shown in the figure. The results show that the battery capacities corresponding to Example 2, Example 4 and Example 6 are around 0.55Ah, while the battery capacity of the comparative example is slightly lower at 0.49Ah.
[0055] 4. The positive electrode sheets obtained in Example 2, Example 4 and Example 6 and the positive electrode sheets obtained in the comparative example were assembled into 0.5Ah batteries and subjected to 1000C pulse discharge
[0056] Test results such as Figure 3As shown. The research results show that the pulse power of Example 2, Example 4 and Example 6 is not much different, while the pulse power of the comparative example is smaller. This is mainly because the addition of the dispersant polypropylene organic solvent evens out the conductive agent in the positive electrode sheet to form a three-dimensional conductive network, allowing lithium ions and electrons to propagate quickly and reduce polarization, thereby improving the power performance of the battery.
Claims
1. A method for preparing a positive electrode slurry, characterized in that The steps involved are as follows: S1, dry mixing: adding the positive electrode active material, the conductive agent and the binder, stirring and mixing to obtain a powder, and then adding N-methyl-2-pyrrolidone to knead to obtain a dough; S2. Wet mixing: Add a dispersant and N-methyl-2-pyrrolidone to the powder mass obtained in S1 and stir to obtain a positive electrode slurry.
2. The method for preparing a positive electrode slurry according to claim 1, characterized in that: The mass ratio of the positive electrode active material, the conductive agent and the binder is 88-98:1-6:1-6; The positive electrode active material is selected from one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, and nickel cobalt lithium manganese oxide; The conductive agent is selected from one or more mixtures of carbon nanotube powder, carbon nanotube dispersion, conductive carbon black, conductive graphite, acetylene black, and graphene; The adhesive is polyvinylidene fluoride.
3. The method for preparing a positive electrode slurry according to claim 1, characterized in that: The amount of N-methyl-2-pyrrolidone added in S1 is 75% of the amount of the powder.
4. The method for preparing a positive electrode slurry according to claim 1, characterized in that: The dispersant in S2 is polyolefin diluted with N-methyl-2-pyrrolidone, and the volume ratio of polyolefin to N-methyl-2-pyrrolidone is 1:500-2000.
5. The method for preparing a positive electrode slurry according to claim 1, characterized in that: The final liquid-to-solid ratio in S2 was 45%, and the stirring speed during the addition was 70 rpm for rotation and 3000 rpm for revolution, and the time was 3 hours.
6. The method for preparing a positive electrode slurry according to claim 1, characterized in that: The viscosity of the positive electrode slurry in S2 is 5000-8000 mPa.s.
7. The method for preparing a positive electrode slurry according to claim 1, characterized in that: The positive electrode active material, conductive agent and adhesive in S1 are added to the mixer twice for mixing, with an interval of 30 minutes. The stirring speed during the addition is 30 rpm for revolution and 500 rpm for rotation. After all the powders are added to the mixer, dry mix them at a speed of 30 rpm for revolution and 4000 rpm for rotation for 60 minutes; the stirring speed during kneading is 70 rpm for revolution and 3000 rpm for rotation, and stir for 4 hours.
8. A positive electrode slurry, characterized in that The method is prepared by any one of claims 1 to 5.
9. A lithium battery positive electrode plate, characterized in that: The positive electrode slurry according to claim 8 is coated on the surface of the current collector and dried.
10. A lithium battery positive electrode according to claim 9, characterized in that: The lithium battery positive electrode sheet is obtained by using the positive electrode slurry that has passed through a 200-mesh sieve, placing it on a coating machine to double-side coat an aluminum foil current collector, passing through three temperature zones and then drying, wherein the temperatures in the three temperature zones are 85°C, 90°C, and 80°C, respectively; the drying temperature is 140°C, and the drying time is 48 hours.
Citation Information
Patent Citations
Lithium ion battery positive electrode slurry, preparation method thereof and lithium ion battery
CN110797536A